Karakteristik Siswa, Daya Terima, dan Kesesuaian Standar Porsi dengan Angka Kecukupan Gizi pada Penyelenggaraan Makan Siang di SD Al Furqan Kabupaten Jember: Student Characteristics, Acceptability, and Suitability of Portion Standards with Recommended Dietary Allowance in School Meals at Al Furqan Primary School, Jember Regency - Sulistiyani; Fitriani, Janiyah Intan (Amerta Nutrition, 2024)
Background: The school food program has the potential to contribute 30% of the total calories. The small size of students' lunch portions reduces their nutrient intake. SD Al Furqan Jember is an elementary school that has been implementing lunch programs for almost a decade. However, we have not yet assessed the appropriateness of the portions provided to students. Objectives: This study aims to describe the student characteristics, acceptability, and suitability of portion standards in food provision at SD Al-Furqan Jember. Methods: This research was descriptive and employed a cross-sectional methodology. The sample consisted of 61 respondents, while the population of this study consisted of 120 sixth-grade students who attended school lunch. Results: The findings indicated that the nutritional status of 40 students was normal, and there was a greater number of female students than male students among the 11-12-year-old respondents. Students generally found the food to be acceptable, with the third menu being the most preferred (crisp chicken) and the eighth menu being the least preferred (sour vegetables). The portion standards from 20 menu cycles were primarily not in accordance with 30% of AKG. The energy, protein, fat, and carbohydrate categories were not aligned with 18 menus, 17 menus, 16 menus, and 16 menus for female students, and 14 menus, 13 menus, 16 menus, and 17 menus for male students. Conclusions: The Crispy Chicken Menu is the most popular. The standard portion of each menu is primarily not in accordance with AKG.